HIV Viremia Is associated With APOL1 Variants and Reduced JC-Viruria (2021)
Variants in the Apolipoprotein L1 (APOL1) gene (G1-rs60910145, rs73885319, G2-rs71785313) are common in Africans and in individuals of recent African ancestry and are associated with an increased risk of non-diabetic chronic kidney disease (CKD) and in particular of HIV associated nephropathy (HIVAN). In light of the significantly increased risk of HIVAN in carriers of two APOL1 risk alleles, a role in HIV infectivity has been postulated in the mechanism of APOL1 associated kidney disease. Herein, we aim to explore the association between HIV viremia and APOL1 genotype. In addition, we investigated interaction between BK and JC viruria, CKD and HIV viremia. A total of 199 persons living with HIV/AIDS (comprising 82 CKD cases and 117 controls) from among the participants in the ongoing Human Heredity and Health in Africa (H3Africa) Kidney Disease Research Network case control study have been recruited. The two APOL1 renal risk alleles (RRA) genotypes were associated with a higher risk of CKD (OR 12.6, 95% CI 3.89–40.8, p < 0.0001). Even a single APOL1 RRA was associated with CKD risk (OR 4.42, 95% CI 1.49–13.15, p = 0.007). The 2 APOL1 RRA genotypes were associated with an increased probability of having HIV viremia (OR 2.37 95% CI 1.0–5.63, p = 0.05). HIV viremia was associated with increased CKD risk (OR 7.45, 95% CI 1.66–33.35, P = 0.009) and with a significant reduction of JC virus urine shedding (OR 0.35, 95% CI 0.12–0.98, p = 0.046). In contrast to prior studies, JC viruria was not associated with CKD but was restricted in patients with HIV viremia, regardless of CKD status. These findings suggest a role of APOL1 variants in HIV infectivity and emphasize that JC viruria can serve as biomarker for innate immune system activation.